Influence of Nb content on the mechanical behavior of zirconium alloys. Issue 1 (1st October 2022) - Pang, C; Li, H; Zhao, W L; Zhang, C H
Abstract: Zirconium alloys are basically used in the core structural components of a nuclear reactor. For further understanding mechanical behaviors of zirconium alloy, several alloys with various Nb content are investigated. Microstructure observation, Vickers hardness and mechanical stress-strain curves have been investigated and numerically extracted. Conclusions confirm that the precipitation content of the second phases in Zr-Sn-Nb-Fe-Cr alloys increases with the gradual increment of Nb content. When Nb content reaches to 1.2 wt.%, the excess Nb participates in the formation of second phase containing Nb, which increases the amount of second phases. Moreover, the increase of alloy strength and hardness is mainly attributed to the precipitation strengthening mechanism of second phases.